Central Venous Pressure Correlates with Inferior Vena Cava Collapsibility Index in Patient Treated in Intensive Care Unit - Wiryana, Made; Sinardja, I Ketut; Aryabiantara, I Wayan; GdeAgung Senapathi, Tjokorda; Gede Widnyana, I Made; Mahaalit Aribawa, I Gusti Ngurah; Gede Utara Hartawan, I Gusti Agung; Parami, Pontisomaya; Perangin Angin, Emkel (Bali Journal of Anesthesiology, 2017)
Background: Intravascular volume status is an important parameter in monitoring the patients treated at intensive care unit (ICU), so accuracy and strict monitoring of fluid volume is one factor that influence patientâs health status. Amongst others, two ways to monitor body fluid volume status is central venous pressure (CVP) and collapsibility index of inferior vena cava (IVC) diameter. The purpose of this study is to determine the correlation between CVP with the IVC collapsibility index in patients treated in ICU Sanglah Hospital in Denpasar. Method: Seventy patients treated at Sanglah Hospital ICU with already inserted CVC for appropriate indication, were measured for CVP, then followed by examination the diameter of IVC with ultrasound to measure the maximum and minimum collapsibility index. Spearmanâs correlation coefficients was used to assess the correlation between CVP and collapsibility index of the IVC. Results: In 70 patients, we found a very strong negative correlation between CVP and IVCâs collapsibility index (Spearmans rho = -0.854; p <0.001). Conclusion: This study found that there is a very strong negative correlation between CVP and collapsibility index of IVC. This finding indicates that the collapsibility index of the IVC may substitute CVP in determining the status of the intravascular volume.